The auxiliary information-based double EWMA control chart for the process means in short production runs - Goh, Sook Yan (2023)
Control charts are essential tools in ensuring the quality of products and services by monitoring the production process. Control charts can be classified into two types which include memoryless and memory-type control charts. The EWMA control chart is a well-known memory-type chart in detecting small to moderate shift sizes. Short production runs are commonly applied in high-mix, low production manufacturing environments such as job shops with a variety of production items with small production runs of products and limited inspection time. The objective of this study is to investigate the performance of the auxiliary information-based double EWMA (DEWMA-AI) control chart in short production runs. The proposed chart is compared with the existing auxiliary information-based charts,